Solitary median maxillary central incisor – case report - Molska, Magdalena; Janiszewska, Jagoda; Mikołajczyk, Marcin; Małkiewicz, Konrad (Forum Ortodontyczne / Orthodontic Forum, 2018)
Solitary Median Maxillary Central Incisor Syndrome (SMMCI Syndrome) is a rare developmental disorder consisting of morphological defects that mainly affect structures in the midline of the body. The aetiology of this syndrome has not been fully explained, and SMMCI syndrome is observed more frequently in females. The presence of a solitary median maxillary incisor in the midline of the maxilla is a typical trait in the stomatognathic system, and this anomaly is found in both deciduous and permanent dentition. Regarding developmental abnormalities accompanying a solitary incisor with an atypical structure, the most common ones include: lack of the frenulum of the upper lip, deformations in the nasal cavity and cranial base, heart defects, cleft lip and palate, and mental disability of various severity. Aim. The aim of this work is to present the characteristic traits of a solitary median maxillary central incisor syndrome on the basis of a case study of a 9-yearold female patient and the analysis of available literature. Material and methods. The literature review was performed using the PubMed database and the following key words: incisor, maxilla, syndrome, development, SMMCI syndrome. Case report. When the clinical examination and medical history were performed the patient was diagnosed with signs of solitary median maxillary central incisor syndrome. The outcomes of a computed tomography scan confirmed choanal stenosis. Except for allergies to animal hair and grass, the patient did not suffer from any systemic diseases. On the basis of a clinical examination and analysis of additional tests the following diagnosis was made: I skeletal class, complete distocclusion with incisor protrusion, partial lateral bilateral cross bite and dental abnormalities. Summary. Patients diagnosed with SMMCI syndrome often require complex care provided by specialists from various fields of medicine and dentistry, due to the possibility of coexistence of numerous developmental abnormalities involving different body structures. (Molska M, Janiszewska J, Mikołajczyk M, Małkiewicz K. Solitary median maxillary central incisor – case report. Orthod Forum 2018; 14: 333-43).